JAPAN’S AGING SOCIETY: POLICY, LESSON AND THE SILVER ECONOMY - Siriporn Dabphet (PEOPLE: International Journal of Social Sciences, 2025)
This paper examines policies and lessons learned from Japan’s aging society and the potential of the silver economy. Through documentary research, the findings indicate that Japan’s population is aging more rapidly than in other countries, having transitioned into an aging society since the 1970s and subsequently into a super-aged society—the oldest in the world. This demographic shift has significant economic and social implications. In response, Japan has implemented various policies and preparations to address its aging population. These aging strategies are proactive and effective initiatives undertaken by both the public and private sectors. Public healthcare systems, including medical treatment, pension insurance, and home care services, have been established and continuously improved. The aging society has led to a reduction in the number of young workers, a decline in personal income tax revenue, and an increase in government expenditure on elderly welfare. The growing elderly population in Japan is reshaping the economy and consumption patterns. Both governmental sectors and private businesses are developing products, innovations, and services tailored to elderly individuals, known as the silver economy. This trend is not confined to Japan; other countries can also benefit from Japan’s aging society.